PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DENGAN MODEL SEARCH, SOLVE, CREATE, SHARE (SSCS) BERBASIS ETNOSAINS DAN BERPIKIR KRITIS PADA MATERI EKOLOGI KELAS X SMA - Wahyu Rakhma Dhanti; Yuslim Fauziah; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to develop the Student Training Worksheet (LKPD) with the ethnics-based Search, Solve, Create, Share (SSCS) model and critical thinking on the high school class X ecological material in March-December 2019. The research was conducted in two places, namely to LKPD validation was conducted at the FKIP UNRI Biology Education Campus and LKPD limited trials were conducted at SMAN 15 Pekanbaru. This type of research refers to the R&D research approach using the ADDIE model developed by Dick and Carry. The subject of this research is the subject matter of Biology in high school class X KD 3.10. The developed LKPD consisted of 2 meetings (1 week = 3 JP) with a time allocation of 1 JP for 45 minutes. The parameters of this study include the results of the validation of the development of LKPD by the validator, limited test assessment and critical thinking skills assessment. The assessment is done using a validation sheet and a questionnaire. Data analysis is descriptive qualitative and quantitative. The results of this study indicate that LKPDs that have been developed are in the very valid category with an average score of all aspects of 3.46, the value of the results of trials I and II in all aspects obtained an average score of 3.63 and 3.42 with very good categories. The value of the answers to students' critical thinking skills at LKPD meetings 1 and 2 are 93 and 93.8 with very good categories. Based on the results of the validation, the results of the first trial, the results of the second trial and the revisions that have been made, LKPD is good and feasible to be used as a reference at school learning to increase students' knowledge and understanding of ecological material.Key Words: Critical Thinking , Ethnoscience, Student Worksheets, Model Search, Solve, Create, Share (SSCS)